Punctuation marks as stylistic markers in Latvian and British corpora - Ķauķīte, Sintija (Baltistica, 2021)
Text is made of different signs, e.g., graphical signs – punctuation marks and emoticons. Punctuation has four functions in the written language: grammatical, intonative, semantic, and stylistic. Since the Latvian language uses the same punctuation marks as English and also the language features in fiction and mass media have become more important, the paper analyses the stylistic usage of punctuation marks in Latvian and English corpora.
Keywords: Latvian; British; punctuation; corpora; stylistic usage